Revisit moderating role of religiosity for celebrity endorsement and advertising effectiveness in tourism sector / Nor Faiz Azizan - Azizan, Nor Faiz (2023)
Malaysia is one of many countries where celebrities are commonly featured in advertisements to promote products to consumers through traditional and social media platforms. In this digital age, scholars are debating about whether celebrity endorsement can translate to effective advertising. Religion has become a significant factor because it can lead to a desire for responsible consumption. In the context of consumerism, religiosity can facilitate Muslim consumers' purchasing decisions since Islam encourages its adherents to follow Sharia values as a way of life. Based on a survey of 300 Muslim consumers, the findings revealed that religiosity moderates the positive effect of celebrity endorsement on advertising effectiveness. Specifically, the impact of celebrity endorsement on advertising effectiveness is greater when the religiosity level is high rather than low. From a practical standpoint, marketers should prioritise the celebrity selection process to comply with the teachings of Islam.